Institutional educative management project based on competences for the training of health technicians - Manuel Roberto Tolozano Benites; Maribel Ferrer Vicente; Jorge Forgas Brioso (Centro Provincial de Información de Ciencias Médicas, 2017)
Different representative practices of technical and technological education in health have been evidenced in Ecuador. Programs, in a greater or lesser extent, have been broken up, so they do not respond to the common developed and educative projects. Taking into account the limited tradition and experience in the elaboration of these projects and the absence of an explicit public politics that goes beyond the rules of LOES implementation, either the professors staff or other decision actors, have found great difficulties to assume the challenge. Therefore, the critical analysis of the Bolivian Technological Institute situation, as well as the empirical investigations carried out, allowed the investigators to elaborate an institutional educative management project.